Effects of substrate type on denitrification efficiency and microbial community structure in constructed wetlands. (July 2020) - Fu, Guiping; Wu, Jinfa; Han, Jingyi; Zhao, Lin; Chan, Ging; Leong, Kunfong
Graphical abstract: Highlights: Sand + activated carbon + ceramsite removed 97.4 of NH4 + -N and 96.2% of TN. Ceramsite + activated carbon + sand substrate had a high DO content. NH4 + -N removal was improved by AOB, anammox, and aerobic denitrifying bacteria. Lightweight substrates had high bacterial abundance, e.g ., Vibrio and Planctomyces. Abstract: Three constructed wetland systems were established to treat saline sewage via high-porosity ceramsite, activated carbon, and low-porosity sand: A (ceramsite + activated carbon + sand), B (sand + activated carbon + ceramsite), and C (sand). The distribution of dissolved oxygen in these systems varied with different filling methods with the best removal efficiency of ammonium nitrogen and total nitrogen observed in system B (97.4 and 96.2%, respectively). The 16S rDNA amplicon sequencing results showed that all the systems had a high abundance of salt-tolerant denitrifiers, and the filling method significantly impacted denitrifying bacteria (e.g., Vibrio and Planctomyces ) in the substrate. System B had more diverse dissolved oxygen conditions than system A and showcased aerobic nitrification–denitrification and anaerobic ammonium oxidation pathways. Therefore, the use of substrates with different porosities can improve the dissolved oxygen supply and enhance nitrogen removal efficiency in constructed wetlands.